Ambivalent Change in CDS Spreads in 11 Euro Area Countries - Török, László (Public Finance Quarterly, 2022)
One of the macroeconomic consequences of the COVID-19 epidemic is that the global economy has seen a robust increase in the countries‘ gross external debt and the sovereign public debt that is part of it. Nor have the eurozone Member States escaped this effect. The increase in gross external debt and sovereign government debt also means that it has become theoretically more risky for investors to buy debt securities (typically bonds). Theoretically, however, it follows that as a result of the increase in risks in the country, CDS spreads had to rise as well. The study uses a correlation calculation to show that the development of the price of CDSs is more closely correlated with gross government debt than with gross external debt. Using hierarchical cluster analysis, the study groups the countries of the Eurozone. The basis for clustering is the close relationship between a country‘s gross government debt and its CDS spread over the period under review. A relevant conclusion of the study is that the increase in gross government debt was not followed by an increase in CDS spreads because the financial source of the increase in government debt was different from previous years.